2012
DOI: 10.1111/j.1530-0277.2012.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death 4 (PDCD4): A Novel Player in Ethanol‐Mediated Suppression of Protein Translation in Primary Cortical Neurons and Developing Cerebral Cortex

Abstract: Background Prenatal exposure to ethanol elicits a range of neuro-developmental abnormalities, microcephaly to behavioral deficits. Impaired protein synthesis has been connected to pathogenesis of ethanol-induced brain damage and abnormal neuron development. However, mechanisms underlying these impairments of protein synthesis are not known. In this study, we illustrate the effects of ethanol on programmed cell death protein 4 (PDCD4), a tumor and translation repressor. Methods Primary cortical neurons (PCNs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 62 publications
(83 reference statements)
1
40
0
Order By: Relevance
“…One study that appeared after Kennedy's (1984) review demonstrated that protein synthesis rates were significantly reduced in the brains of EtOH‐exposed rat embryos (Rawat, ). This was further confirmed in more recent studies, which established that the rate of protein synthesis reduction in the brain can be as much as 40% (Bonner et al., ; Narasimhan et al., ). The results of our meta‐analyses are consistent with this hypothesis: we found enrichment of genes involved in ribosome biogenesis (or more generally ribonucleoprotein complex biogenesis) in our down‐regulated “all,” “acute,” and “prenatal” meta‐signatures.…”
Section: Discussionmentioning
confidence: 55%
“…One study that appeared after Kennedy's (1984) review demonstrated that protein synthesis rates were significantly reduced in the brains of EtOH‐exposed rat embryos (Rawat, ). This was further confirmed in more recent studies, which established that the rate of protein synthesis reduction in the brain can be as much as 40% (Bonner et al., ; Narasimhan et al., ). The results of our meta‐analyses are consistent with this hypothesis: we found enrichment of genes involved in ribosome biogenesis (or more generally ribonucleoprotein complex biogenesis) in our down‐regulated “all,” “acute,” and “prenatal” meta‐signatures.…”
Section: Discussionmentioning
confidence: 55%
“…Our laboratory has previously shown that PDCD4 plays a critical role in ethanol-induced dysregulation of protein synthesis in PCNs and in utero binge alcohol model [11]. Since neuron development is progeny dependent, in the current study we investigated whether ethanol-induced PDCD4 changes are conserved in mitotic neuroblasts, the immediate precursor of neurons.…”
Section: Resultsmentioning
confidence: 95%
“…This is a well-established and documented primary neuronal culture system, which is essentially free of glia. Dual immunostaining with MAP2 (for neurons) and GFAP (for astrocytes) were performed and the isolation procedure reproducibly adopted yielded ~95% enriched neuronal culture [4,29]. Handling of animals was carried out according to the National Institutes of Health guidelines for the use and care of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro experiments involving ETOH in the current study uses a clinically relevant dose, which is at or below to that used in other studies to elicit a range of neurotoxic responses including brain apoptotic responses in various neuron culture, mouse and rat models [4,23,29,30]. …”
Section: Methodsmentioning
confidence: 99%